2014
DOI: 10.25011/cim.v37i3.21379
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose ketamine pretreatment reduces oxidative damage and inflammatory response following CO2 pneumoperitoneum in rats

Abstract: Low-dose ketamine pretreatment reduces oxidative damage and in ammatory response following CO2 pneumoperitoneum in rats AbstractPurpose: e duration of pneumoperitoneum during laparoscopic procedures may contribute to post-surgical oxidative stress. Previous studies have shown that low-dose ketamine, an anesthetic with anti-in ammatory properties, protects various organs from ischemia-reperfusion injury. is study investigated the e ects of low-dose ketamine on the overproduction of oxidants and the tissue damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
1
Order By: Relevance
“…With the applied procedure (i.e., 25, 30, 40, or 50 mmHg intra-abdominal hypertension), there was a regular downhill chain of events, regardless of the type of anesthesia (i.e., esketamine, as ketamine is an antioxidant ( Xingwei et al, 2014 ) that may provide a more prolonged survival period than thiopental). The abdominal wall compliance threshold was crossed mechanically, with no further stretch of the abdomen; this increased intra-abdominal pressure, compressed vessels and organs, and pushed up the diaphragm as a predetermined definitive outcome ( Depauw et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the applied procedure (i.e., 25, 30, 40, or 50 mmHg intra-abdominal hypertension), there was a regular downhill chain of events, regardless of the type of anesthesia (i.e., esketamine, as ketamine is an antioxidant ( Xingwei et al, 2014 ) that may provide a more prolonged survival period than thiopental). The abdominal wall compliance threshold was crossed mechanically, with no further stretch of the abdomen; this increased intra-abdominal pressure, compressed vessels and organs, and pushed up the diaphragm as a predetermined definitive outcome ( Depauw et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the applied procedure (i.e., 25, 30, 40, or 50 mmHg intraabdominal hypertension), there was a regular downhill chain of events, regardless of the type of anesthesia (i.e., esketamine, as ketamine is an antioxidant (Xingwei et al, 2014) that may provide a more prolonged survival period than thiopental). The abdominal wall compliance threshold was crossed mechanically, with no further stretch of the abdomen; this FIGURE 7 | Gastrointestinal lesions microscopy scoring (0-15), stomach, duodenum, jejunum, ascending colon and intestinal villi high, µm, and stomach lesions (sum of longest lesions diameters, mm), relative liver weight (% of total body weight), relative spleen weight (% of total body weight) in the thiopental-anesthetized rats with the increased intra-abdominal pressures at 50 mmHg for 25 min, at 30 mmHg or 40 mmHg for 30 min, at 25 mmHg for 60 min increased intra-abdominal pressurestime, and in the esketamine-anesthetized rats with the increased intra-abdominal pressures at 25 mmHg for 120 min increased intra-abdominal pressures-time, following medication (BPC 157 10 μg/kg (light gray bars), 10 ng/kg (dark gray bars); saline 5 ml/kg (white bars)) given subcutaneously at 10 min increased intraabdominal pressures-time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ketamine has immunomodulatory effects on nitric oxide (NO) production [ 7 , 21 , 22 ], macrophage and microglial function [ 17 , 23 , 24 ], neutrophil activation and migration [ 6 , 25 28 ], and other immune cells, mediators, and pathways [ 29 33 ]. These studies demonstrated that ketamine has a wide range of effects on the immune system, thus highlighting the importance of determining the drug’s overall impact on inflammation for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CO 2 pneumoperitoneum can cause negative effects on body health. Splanchnic organs such as liver, kidneys, spleen, intestine, ovaries and testicles are susceptible to pneumoperitoneum adverse effects [ 6 , 26 30 ]. The liver receives blood supply from the hepatic artery and portal vein and it is one of the most susceptible organs affected by ischemia.…”
Section: Discussionmentioning
confidence: 99%